Screening of soybean genotypes for resistance to pod sucking bug, Riptortus linearis - AYDA KRISNAWATI; MARIDA SANTI YUDHA IKA BAYU; M. MUCHLISH ADIE (Smujo International, 2017)
Krisnawati A, Bayu MSIY, Adie MM. 2017. Screening of soybean genotypes for resistance to pod sucking bug, Riptortus linearis. Nusantara Bioscience 9: 181-187. Pod sucking bug, Riptortus linearis, is potentially harmful pest of soybean in Indonesia. The development of resistant variety is one of the major goal in soybean breeding. The research aimed was to identify the resistance of soybean genotypes to pod sucking bug. The experiment was conducted in Indonesian Legumes and Tuber Crops Research Institute’s screen house from March to June 2015. The experiment was arranged in Randomized Complete Block Design using 10 soybean genotypes with three replicates. The resistance was evaluated by choice and no-choice test. Data collected on some agronomic characters, number of damaged pod/plant, and number of damaged seed/plant. The resistance criteria determined by using the method from Chiang and Talekar (1980). The results showed that the lowest percentage of pod and seed damage was found on G511H/Anjasmoro//Anjasmoro-2-8 in both no-choice and choice test. In the no-choice test, the lowest percentage of pod and seed damage were 25.83% and 19.12%, respectively. In the choice test, the lowest percentage of pod and seed damage were 25.02% and 20.02%, respectively. The grouping of resistance genotypes based on the no-choice test as well as choice test, the genotype G511H/Anjasmoro//Anjasmoro-2-8 showed a consistently resistant. This genotype could be used as a resistant donor in the soybean breeding program for resistance to pod sucking bug.